A Guidance and Counseling-Based Care System In Boarding School Care In Developing Intellectual Independence (Research at Riyadul Ulum Wadda'wah Condong Islamic Boarding School and Al Amin Islamic Boarding School in Tasikmalaya City) - Wildan Mahmudin; Ajid Thohir; Dudy Imanuddin Effendi; Abdul Rozak (MASI Mandiri Edukasi, 2026)
Islamic boarding schools (pondok pesantren) play an important role in shaping students’ character, spirituality, and intellectual development. In addition to providing religious education, pesantren also support the development of students’ intellectual independence through higher-order thinking skills (HOTS). This study aims to analyze the integration of caregiving systems, guidance and counseling services, HOTS development, and intellectual independence at Riyadul Ulum Wadda’wah Islamic Boarding School and Al Amin Islamic Boarding School. The novelty of this study lies in examining how caregiving practices in pesantren are integrated with guidance and counseling approaches to foster students’ intellectual independence and critical thinking abilities. This study employed a qualitative case study approach. Data were collected through observations, interviews, and documentation involving caregivers, teachers, counselors, and students. The findings show that guidance and counseling–based caregiving systems support the development of students’ intellectual independence by encouraging analytical, evaluative, and creative thinking in both academic and daily life contexts. Counseling activities, mentoring, and disciplined caregiving practices also help students develop problem-solving skills, self-confidence, and independent decision-making. The study concludes that integrating caregiving, counseling, and HOTS-oriented learning can strengthen students’ intellectual independence within the pesantren educational environment.